Accelerated pericyte degeneration and blood–brain barrier breakdown in apolipoprotein E4 carriers with Alzheimer’s disease - Halliday, Matthew R (J Cereb Blood Flow Metab, 2016)
The blood–brain barrier (BBB) limits the entry of neurotoxic blood-derived products and cells into the brain that is required for normal neuronal functioning and information processing. Pericytes maintain the integrity of the BBB and degenerate in Alzheimer’s disease (AD). The BBB is damaged in AD, particularly in individuals carrying apolipoprotein E4 (APOE4) gene, which is a major genetic risk factor for late-onset AD. The mechanisms underlying the BBB breakdown in AD remain, however, elusive. Here, we show accelerated pericyte degeneration in AD APOE4 carriers >AD APOE3 carriers >non-AD controls, which correlates with the magnitude of BBB breakdown to immunoglobulin G and fibrin. We also show accumulation of the proinflammatory cytokine cyclophilin A (CypA) and matrix metalloproteinase-9 (MMP-9) in pericytes and endothelial cells in AD (APOE4 >APOE3), previously shown to lead to BBB breakdown in transgenic APOE4 mice. The levels of the apoE lipoprotein receptor, low-density lipoprotein receptor-related protein-1 (LRP1), were similarly reduced in AD APOE4 and APOE3 carriers. Our data suggest that APOE4 leads to accelerated pericyte loss and enhanced activation of LRP1-dependent CypA–MMP-9 BBB-degrading pathway in pericytes and endothelial cells, which can mediate a greater BBB damage in AD APOE4 compared with AD APOE3 carriers.